Initial events in the colonisation of tomatoes by Oidium lycopersici, a distinct powdery mildew fungus of Lycopersicon species - Jones, H; Whipps, J; Thomas, B; Carver, T; Gurr, S (2000)
The rDNA intergenic spacer sequence of Oidium lycopersici (ana.: Cooke and Massee 1888. emend. Noordeloos and Loerakker 1989, emend. Mieslerova and Lebeda 1999) was determined and compared with the sequences of other powdery mildews. This pathogen was shown to be distinct from other powdery mildew fungi found on tomato, but it exhibited a close similarity to Erysiphe aquilegiae var. ranunculi. The initial events involved in the germination of conidia and subsequent formation of the appressorium in the newly described powdery mildew of tomato. O. lycopersici. were studied by light and scanning electron microscopy. Scanning electron microscopy revealed the conidial coat to be smooth to slightly rugose and the appressoria to be multilobed and attached to the host by a mucilaginous pad of extracellular material.